Concordance of Colposcopy-Directed Biopsy and Conization Results in Cervical Dysplasia - Alan, Cemre; Metin, Ulfet Sena; Acar, Ali (Gynecology Obstetrics & Reproductive Medicine, 2025)
OBJECTIVE: Cervical cancer prevention requires proper management of women with cervical intraepithelial neoplasia (CIN). A colposcopy is key to diagnosing CIN in women with abnormal cytology. Colposcopy identifies lesions, assesses grading, and guides biopsies. Excisional procedures like cold knife conization remove affected tissue for pathological examination and treat the CIN lesions. Some studies evaluate the consistency of conization and colposcopy-directed biopsy results. This study aimed to review the data of patients who had undergone conization retrospectively and to assess the consistency in predicting malignancy between preoperative cytology, biopsy, and/or Human papillomavirus (HPV) findings and conization pathologies. STUDY DESIGN: This retrospective study included 114 women presenting to the gynecological oncology department between 2013 and 2024. The study included women with abnormal cytology and/or positive HPV 16/18 or persistent positivity for other high-risk HPV types. All of the women had undergone a colposcopy-directed biopsy and conization procedure. The kappa statistic (k) was used to assess the correlation between colposcopy-directed biopsy and conization findings. RESULTS: Among the patients, 46 (40.35%) had concordant colposcopy-directed biopsy and pathology results. The strength of agreement, as indicated by the Kappa statistic, was 0.237 (p<0.001). Colposcopy sensitivity for detecting high-grade cervical pathology was 93.2%, and specificity was 40%. of 77 patients (67.5%), an agreement between colposcopy-directed biopsy and cervical pathology for low and high-grade lesions was observed. The strength of agreement with the Kappa statistic was 0.338 (p<0.001). CONCLUSION: This study showed that with a sensitivity of over 90%, colposcopy-directed biopsy plays an important role in detecting high-grade cervical lesions.